这是方程?貌似没等号的说
(x2+3x+9)/(x2-27)+(6x)/(9x-x2)-(x-1)/(6+2x)
2个回答
相关问题
-
x2+3x+9/x2-27+6x/9x-x2-x-1/6+2x 化简
-
求化简:(x^2+3x+9)/(x^2-27)+(6x)/(9x-x^2)-(x-1)/(6+2x)
-
(x^2+3x+9)/(x^2-9)+6x/(9x-x^2)-(x-1)/(6+2x)
-
化简~化简~(x²+3x+9/x²-27)+(6x/9x-x²)-(x-1/6+2x)
-
观察以下等式:(x+1)(x2-x+1)=x3+1(x+3)(x2-3x+9)=x3+27(x+6)(x2-6x+36)
-
9^-x-2.3^1-x=27还有一道,6^x+4^x=9^x
-
(1)2x/9-x² + 1/x-3 + 2/x²+6x+9
-
计算:1/(x+1) * [(x-3)/(x^2 + 6x + 9) + 2/(3+x)] - x/(x^2 - 9)
-
(1-x/3-x)^2÷(x^2-6x+9/9-x^2)*1/x^2-2x+1
-
计算:(1)x2+9xx2+3x+x2−9x2+6x+9